Innovation in Islamic Religious Education in The Digital Era for Students' Religious Tolerance Character Building in Elementary School: An Implementation of Beyond the Wall Learning Model - Elga Yanuardianto; Djoko Rohadi Wibowo; Prima Cristi Crismono (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The digital era has brought significant changes to various aspects of life, including education. This article explores innovations in Islamic religious education that leverage digital technology to foster religious tolerance among students. Through the